Uji Potensi Triterpenoid dari Kulit Batang Waru Jawa (Hibiscus tiliaceus L.) sebagai Kandidat Antiinflamasi pada Mencit (Mus musculus) Model Rheumatoid Arthritis Berbasis in Silico - Lisa Savitri; Elfred Rinaldo Kasimo; Datin An Nisa Sukmawati; Syntia Tanu Juwita; Eka Wahyuningtiyas; Ana Retnowati (Jurnal Ilmiah Universitas Batanghari Jambi, 2021)
Waru jawa (Hibiscus tiliaceus L.) is a plant that functions as an anti-inflammatory. Compounds from the waru jawa plant, especially the bark can be grouped into alkaloids, flavonoids, triterpenoids, and steroids. The content of triterpenoids from the waru jawa stem bark was tested for their biochemical activity, so that it is expected that the bark of Javanese waru stems can be used optimally. This study aims to determine the potential of triterpenoids from waru jawa stem bark as anti-inflammatory candidates in mice (Mus musculus) rheumatoid arthritis model in silico-based. Potential analysis of triterpenoids in mice was carried out using the STITCH, which is a database of known and predicted interactions between chemicals and proteins found in living things. Interactions in question are physical and functional associations, the data contained in STITCH comes from computational predictions, transfer of knowledge between organisms, and from interactions collected from other databases. Analysis of the triterpenoid mechanism of waru jawa stem bark against rheumatoid arthritis model mice in silico-based using the bioinformatics application Kegg. Based on the results of the analysis, it can be seen that triterpenoids derived from waru jawa stem bark sources play an important role in reducing inflammation. The triterpenoids target NF-κB, leading to its downregulation. Triterpenoids have been found to have many functions, although their effective concentrations for various cellular effects may vary widely. Depending upon the dose administered, triterpenoids can induce anti-inflammatory, proliferation-arresting, apoptotic effects, cytoprotective, and tumor-differentiating.